KINERJA PELAYANAN PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS I KHUSUS TPI MEDAN - Nini Sarah Br Sihombing (Universitas Bina Taruna Gorontalo, 2024)
This research is motivated by the existence of problems in the performance of passport making services at the Medan TPI Special Class I Immigration Office. Some of the problems in the performance of passport making services include procedures that are considered to complicate passport applicants, inadequate number of staff while the number of requests increases which causes queue buildup and there is no guarantee of the timeliness of passport completion given by officers. Furthermore, this study discusses the performance of officers in serving passport making at the Medan TPI Special Class I Immigration Office. The importance of this research is to be able to know the efforts or ways made by the Medan TPI Special Class I Immigration Office in improving the performance of officers in providing services. In addition, this research is also useful for officers at the Immigration Office as service providers to improve and improve their performance in order to achieve goals seen from the level of satisfaction of service users and increase public trust. This research uses descriptive research with a qualitative approach method. Data collection techniques are carried out by observation, interviews, documentation and literature study. The informants in this study were the Head of the Travel Document Section, Travel Document Staff and passport applicants. The results showed the following First, Productivity has been running successfully this is evidenced by the increasing number of passport applicants; Second, Service quality is still not running optimally because there are still complaints; Third, Responsiveness has been running optimally as evidenced by the dexterity of officers in providing services; Fourth, Responsiveness still needs to be improved regarding the guarantee of timeliness of passport completion and Fifth, Accountability has been successful as seen from the transparency indicators in the passport making service process, handling complaints and monitoring and evaluating the performance of officers in serving passport making services.